2020
DOI: 10.1002/ps.5801
|View full text |Cite
|
Sign up to set email alerts
|

Safening activity and metabolism of the safener cyprosulfamide in maize and wheat

Abstract: BACKGROUND Safeners extend the application of existing herbicides by selectively enhancing tolerance in large‐grained cereal crops. While their activity is linked to enhanced herbicide metabolism, their exact mode of action and reasons for their crop specificity have yet to be determined. In this study, we investigated the selectivity of the recently developed sulfonamide safener cyprosulfamide (CSA) in maize (Zea mays L.) and wheat (Triticum aestivum), focusing on its uptake, distribution and metabolism in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
(42 reference statements)
0
24
0
Order By: Relevance
“…26,27 It was shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the benzenesulphonamide group as a chemical feature required for its safener activity. 28 Scaffold hopping and active substructure combination play an important role in drug discovery techniques which are beneficial to the discovery of potential agrochemicals. Scaffold hopping creates new opportunities by incorporating novel scaffolds into known molecules in search of active compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 It was shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the benzenesulphonamide group as a chemical feature required for its safener activity. 28 Scaffold hopping and active substructure combination play an important role in drug discovery techniques which are beneficial to the discovery of potential agrochemicals. Scaffold hopping creates new opportunities by incorporating novel scaffolds into known molecules in search of active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Using herbicides composed of IXF and CSA is a successful path for weed control in conventional and herbicide‐tolerant corn production system 26,27 . It was shown that subtle modifications to the structure of CSA can affect its bioactivity, identifying the retention of the benzenesulphonamide group as a chemical feature required for its safener activity 28 …”
Section: Introductionmentioning
confidence: 99%
“…Many sulfonamides are bioactive and have applications as antibiotics in mammals and as safeners in plants [44]. The safeners metcamifen and cyprosulfonamide used in monocot crops, for example, induce the expression of cytochrome P450s and glutathione transferases, which likely catalyze the detoxification of the herbicide clodinafop-propargyl [45,46]. Quinabactin, which activates the ABA receptors PYR1, PYL 1-3, and PYL5 and confers drought tolerance in Arabidopsis and soybean, also contains a sulfonamide group [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, safener treatments may induce transcriptional activation of specific GST genes and enhance the glutathione S-transferase (GST) expression of the respective enzymes that catalyze the conjugation of herbicides with glutathione (GSH) in crop plants to detoxify them [28]. Besides, detoxifying enzymes, including superoxide dismutase (SOD) and peroxidase (POD), are also involved in the detoxification of some herbicides [18,29].…”
Section: Introductionmentioning
confidence: 99%